INTEGRASI MAQASHID SYARIAH TERHADAP SISTEM PEMERINTAHAN DEMOKRATIS DAN OTORITER DI NEGARA BARU MERDEKA (2) - Sugitanata, Arif; Mustakim, Ahmad; Nuriskandar, Lalu Hendri; Elpipit, Elpipit (AL-BALAD : Jurnal Hukum Tata Negara dan Politik Islam, 2023)
This research aims to identify the effectiveness of democratic and authoritarian systems of government in the context of newly independent states, using Maqashid Shariah theory as an analytical framework. Through a desk study and qualitative research, this research explores how the two systems support or hinder the process of national development, political stability, and the achievement of social and economic progress. The results show that democracy offers freedom, active participation of the people, and social justice that are in line with the principles of Maqashid Sharia. However, it also requires solid institutions and mature political awareness. On the other hand, authoritarian systems offer stability and security, but often at the expense of individual freedom and social justice in the long run. This research suggests that transitioning to democracy or integrating elements of both systems in a hybrid model can be a strategy to achieve a balance between stability and freedom, as well as inclusive and sustainable economic growth. In conclusion, in choosing and implementing a system of government, newly independent countries should pay attention to how the system can support the achievement of Maqashid Shariah's objectives, including the balance between government power and individual freedom, as well as promoting sustainable economic growth and social stability.